Respuestas

2012-12-05T04:58:58+01:00

(2^x+1 + 2^x+2 + 2^x+3) / (2^x-3 + 2^x-2 + 2^x-3)

sacamos factor comun; en el nuemrador es 2^x+1 y en el denominador  2^x-2

    2^x+1 (1 + 2 + 2 ^2)

=_______________________

    2^x-2 ( 2^-1 +1 + 2^-1)

 


 2^(x+1-(x-2))(7)

=____________________

(1/2 + 1 + 1/2)



  2^3(7)

=_________

((1+2+1)/2)



  8*7

=_____

(4/2)



=56/2


=28


2012-12-05T05:06:36+01:00

{2^(X+1)   +2^(X+2)  +2^(X+3)}/{ 2^(x-3)+2^(x-2)+2^(x-3) }=


{ 2^x .  2      +   2^x . 2^2   + 2^x .2^3 ) / (2^x : 2^3   +  2^x:2^2  + 2^x:2^3)=



(2.2^x     +   4.2^x   +   8.2^x)/(2^x: 8    +    2^x:4      +   2^x:8)



´{2.2^x( 1+2+4)}/{ (  2^x  +2.2^x+ 2^x)/8}


2.2^x(7)/ {2^x(1+2+1)/8}


14.2^x    /     2^x(4)/8


14.2^x/  2^x/2


14.2^x  .  2/ 2^ x


28.2^x/2^ x

 

28